Landau theory of free standing and epitaxial ferroelectric film - Musleh, Ahmad M. A. (2009)
Landau-Ginzburg-Devonshire’s (LGD) theory and Landau Khalatnikov’s dynamic equation are used to study the polarization reversal of second order ferroelectric (FE) systems. Teori Landau-Ginzburg-Devonshire (LGD) dan persamaan dinamik Landau- Khalatnikov telah digunakan untuk mengkaji penyongsangan pengkutuban bagi sistem-sistem feroelektrik (FE) tertib kedua.